Analisis Tingkat Kepuasan Pengguna Aplikasi E-Pemustaka Menggunakan Metode End User Computing Satisfaction (EUCS) di MIN 45 Aceh Besar - Safira, Ichsan; Maimun (Jurnal Manajemen Sistem Informasi (JMASIF), 2025)
The development of information technology has had a significant impact on the education sector, especially in library management. The E-Pemustaka application implemented at MIN 45 Aceh Besar aims to facilitate access to library services. This study measures user satisfaction with the E-Pemustaka application using the End User Computing Satisfaction (EUCS) method. EUCS evaluates satisfaction through five dimensions: system quality, information quality, service quality, system impact, and ease of use. Data was collected using questionnaires, interviews, and observations from 100 respondents, including students, teachers, and library staff. The results show that most users are satisfied with the ease of searching for books, the speed of borrowing transactions, and the simple interface of the application. However, some issues, such as inaccurate return date recording and suboptimal book search, need to be addressed. This study provides recommendations for improvement, such as enhancing data accuracy and adding features that meet the users' needs. The E-Pemustaka application is expected to be more effective in supporting library activities and improving user experience in the future.